Thermal functional traits of Antarctic mosses link species identity, nitrogen availability and ecosystem processes - Andrew Forrest Clements; Hannah M. Prather; Angelica Casanova-Katny; Todd N. Rosenstiel; Matthew W. Chmielewski; Becky A. Ball; Sarah M. Eppley (Polar Biology, 2026)

Future Projections of Burned Area in Europe Highlight the Importance of Human Action - Maik Billing; Matthew Forrest; Simon P. K. Bowring; Luke Oberhagemann; Alex N. Neidermeier; Jessica Hetzer; Werner von Bloh; Christoph Müller; Susanne Rolinski; Thomas Hickler; Kirsten Thonicke (Global Change Biology, 2026)
Wildfires are often a natural part of many European ecosystems, but human activities through land use, other socio‐economic factors and climate change have significantly changed how fires behave. Anthropogenic climate change is already intensifying fire‐prone weather and increasing wildfire risk across Europe with risk expected to grow sharply in coming decades. Past experience suggests that human action, such as fuel management and improved fire suppression capacity, can reduce wildfire spread and intensity. However, whether current or future efforts can counter rising risks under continued climate change remains uncertain. In this study, we assess the role of socio‐economic factors and biophysical factors in shaping future fire regimes across Europe. Using two fire models (SPITFIRE and BASE) coupled with the fire‐enabled Dynamic Global Vegetation Model LPJmL, we simulate future burned area under two socio‐economic and greenhouse gas concentration pathways (SSP1‐2.6 and SSP3‐7.0). We also run experiments where socio‐economic factors are held constant to isolate their influence. Our findings show that both biophysical and socio‐economic factors strongly affect future wildfire activity. Fire weather and fire management capacity are important drivers, while population density, vegetation shifts and land use matter more at regional scales. By the end of the century, intensified fire weather alone could increase annual burned area by approximately +39% under a low emission scenario (SSP1‐2.6) and by nearly +192% under a high emission scenario (SSP3‐7.0). Continued improvements in fire management capacity could substantially moderate these increases, reducing burned area by 72%–92% compared to scenarios without these improvements. However, under strong climate change, fire activity still rises in about 55% of Europe's fire prone regions, even if investments in fire management capacity continue at current levels. Overall, improved wildfire management capacity has the potential to greatly limit impacts of worsening fire weather, but may not fully offset strong climate change impacts.

Oases of endemism: Regional aquifer desert springs serve as biodiversity hotspots preserving vulnerable endemic taxa in the Great Basin and Mojave Desert regions - Matthew J. Forrest; Donald W. Sada; Matthew S. Edwards; Robert K. Burton; Richard D. Norris (Limnology and Oceanography, 2026)
Spring ecosystems in arid regions often serve as crucial biodiversity hotspots by providing some of the only reliable sources of surface water. However, anthropogenic activities and climate change have severely degraded spring ecosystems worldwide, emphasizing the need for large‐scale multidisciplinary studies informing conservation efforts. Here, we analyzed characteristics of 1121 widely dispersed springs within the Great Basin and Mojave Desert regions, USA to assess the distribution of endemic animal taxa relative to hydrological, geochemical, and ecological parameters. To our knowledge this is the largest original dataset of springs that has been examined in this manner. Our results revealed that the three broad classes of springs: regional aquifer thermal springs, local aquifer cold springs, and local aquifer geothermal springs can be distinguished by their environmental and physicochemical parameters, taxa present, persistence, and natural and human perturbations. Notably, regional aquifer thermal springs support disproportionate numbers of endemic taxa, likely reflecting their stability and longevity. These patterns are particularly striking considering that these springs have been subjected to extreme anthropogenic exploitation and modifications for centuries and frequently support non‐native taxa. Conversely, local aquifer cold springs, which are often highly disturbed and less persistent, support proportionately fewer endemic taxa. The high abundance of endemic taxa in regional aquifer thermal springs indicates that they represent critical biodiversity hotspots, and efforts to conserve and restore these important ecosystems should be major priorities.

Operationalizing nature recovery to market outcomes - Fabio Favoretto; Matthew J. Forrest; Octavio Aburto Oropeza (Ecological Economics, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Modelling past and future impacts of droughts on tree mortality and carbon storage in Norway spruce stands in Germany - Tim Anders; Jessica Hetzer; Nikolai Knapp; Matthew Forrest; Liam Langan; Merja Helena Tölle; Nicole Wellbrock; Thomas Hickler (Ecological Modelling, 2025)

Pseudo-linkage or real-linkage of rust resistance genes in a wheat-Thinopyrum intermedium translocation line - Jianbo Li; Merrill Ryan; Chongmei Dong; Kerrie L. Forrest; Matthew J. Hayden; Smriti Singh; Yuqi Wang; Nizam Ahmed; Robert A. McIntosh; Peng Zhang (Theoretical and Applied Genetics, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

A comparative analysis of OpenET for evaluating evapotranspiration in California almond orchards - Kyle Knipper; Martha Anderson; Nicolas Bambach; Forrest Melton; Zac Ellis; Yun Yang; John Volk; Andrew J. McElrone; William Kustas; Matthew Roby; Will Carrara; Sebastian Castro; et al. (Agricultural and Forest Meteorology, 2024)

Statistical sampling of missing environmental variables improves biophysical genomic prediction in wheat - Abdulqader Jighly; Thabo Thayalakumaran; Surya Kant; Joe Panozzo; Rajat Aggarwal; David Hessel; Kerrie L. Forrest; Frank Technow; Radu Totir; Mike Goddard; Jennie Pryce; Matthew J. Hayden; et al. (Theoretical and Applied Genetics, 2024)

Are novel or locally adapted pathogens more devastating and why? Resolving opposing hypotheses - Erin L. Sauer; Matthew D. Venesky; Taegan A. McMahon; Jeremy M. Cohen; Scott Bessler; Laura A. Brannelly; Forrest Brem; Allison Q. Byrne; Neal Halstead; Oliver Hyman; Pieter T. J. Johnson; Corinne L. Richards‐Zawacki; et al. (Ecology Letters, 2024)
There is a rich literature highlighting that pathogens are generally better adapted to infect local than novel hosts, and a separate seemingly contradictory literature indicating that novel pathogens pose the greatest threat to biodiversity and public health. Here, using Batrachochytrium dendrobatidis , the fungus associated with worldwide amphibian declines, we test the hypothesis that there is enough variance in “novel” (quantified by geographic and phylogenetic distance) host‐pathogen outcomes to pose substantial risk of pathogen introductions despite local adaptation being common. Our continental‐scale common garden experiment and global‐scale meta‐analysis demonstrate that local amphibian‐fungal interactions result in higher pathogen prevalence, pathogen growth, and host mortality, but novel interactions led to variable consequences with especially virulent host‐pathogen combinations still occurring. Thus, while most pathogen introductions are benign, enough variance exists in novel host‐pathogen outcomes that moving organisms around the planet greatly increases the chance of pathogen introductions causing profound harm.

A deeper dive into the blue economy: the role of the diving sector in conservation and sustainable development goals - Matthew J. Forrest; Fabio Favoretto; Zahidah A. Nisa; Octavio Aburto-Oropeza (Frontiers in Marine Science, 2023)
Attaining an equitable Blue Economy requires reconsidering historical extractive usages of natural ocean capital in favor of more sustainable activities. Scuba diving is an expanding industry, and several examples illustrate how the diving sector has assisted with transitions to sustainable economic activities. In certain countries diving tourism generates revenues comparable with fishing industries, yet the sector remains underrepresented within marine conservation efforts. Therefore, we present five actions tailored to enhance the diving sector’s participation in the Blue Economy: i) Organize the fragmented sector via international associations and federations; ii) Recognize usage rights for natural capital equal to extractive activities; iii) Modernize the sector using technology to improve connectivity and data sharing; iv) Invest in the sector by engaging private and public funding and subsidizing critical infrastructure to enable equitable access; v) Foster a sense of community by training and supporting local leaders, thereby ensuring more equitable participation by including women, indigenous people, and the youth. Diving represents one of the only endeavors that enables citizens to actively support the Blue Economy and help to achieve the United Nations Sustainable Development Goal 14, “Life Below Water”; therefore, the diving sector is uniquely poised to help address conservation goals and sustainable development.

Global biome patterns of the Middle and Late Pleistocene - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2023)
Our primary aim was to assess the hypothesis that distinctive features of the patterns of vegetation change during successive Quaternary glacial–interglacial cycles reflect climatic differences arising from forcing differences. We addressed this hypothesis using 207 half‐degree resolution global biome pattern simulations, for time slices between 800 and 2 ka, made using the LPJ‐GUESS dynamic global vegetation model. Simulations were driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 206 palaeoclimate experiments; four additional simulations were driven using projected future CO 2 concentrations. Climate experiments were run using HadCM3. Using a rule‐based approach, above‐ground biomass and leaf area index of LPJ‐GUESS plant functional types were used to infer each grid cell's biome. The hypothesis is supported by the palaeobiome simulations. To enable comparisons with the climatic forcing, multivariate analyses were performed of global vegetation pattern dissimilarities between simulations. Results showed generally similar responses to glacial–interglacial climatic variations during each cycle, although no two interglacials or glacials had identical biome patterns. Atmospheric CO 2 concentration was the strongest driver of the dissimilarity patterns. Dissimilarities relative to the time slice with the lowest atmospheric CO 2 concentration show the log‐linear relationship to atmospheric CO 2 concentration expected of an index of ecocarbon sensitivity. For each simulation, extent and total above‐ground biomass of each biome were calculated globally and for three longitudinal segments corresponding to the major continental regions. Mean and minimum past extents of forest biomes, notably Temperate Summergreen Forest, in the three major continental regions strongly parallel relative tree diversities, hence supporting the hypothesis that past biome extents played an important role in determining present diversity. Albeit that they reflect the climatic consequences only of the faster Earth system components, simulated potential future biome patterns are unlike any during the past 800 ky, and likely will continue to change markedly for millennia if projected CO 2 concentrations are realised.

Movement drives population dynamics of one of the most mobile ungulates on E arth: Insights from a mechanistic model - Theresa S. M. Stratmann; Matthew Forrest; Wolfgang Traylor; Nandintsetseg Dejid; Kirk A. Olson; Thomas Mueller; Thomas Hickler (Ecology, 2023)
Long‐distance movements are hypothesized to positively influence population size and stability of mobile species. We tested this hypothesis with a novel modeling approach in which moving herbivores interact with the environment created by a dynamic global vegetation model using highly mobile Mongolian gazelles in the eastern Mongolian grasslands as a case study. Gazelle population dynamics were modeled from 1901 to 2018 under two scenarios, one allowing free movement and one restricting movement. Gazelles were 2.2 times more abundant when they could move freely and were extirpated in 71% of the study area when mobility was restricted. Mobility resulted in greater population increases during times of abundant forage and smaller population decreases during drought. Reduced thermoregulatory costs associated with climate change, combined with an increase in vegetation biomass, increased gazelle abundance. Since high abundances often resulted in overgrazing and, thus, extirpation when movement was restricted, mobility had an important role in maintaining higher densities. The novel modeling approach shows how accounting for not just herbivore but also plant ecophysiology can improve our understanding of the population dynamics of highly mobile herbivores, in particular when examining the effects of habitat and climate change. Since the model simulates herbivores based on general physiological mechanisms that apply across large herbivores and the vegetation model can be applied globally, it is possible to adapt the model to other large‐herbivore systems.

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Correction to: Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta‑Espino; et al. (Theoretical and Applied Genetics, 2022)

Haplotype variants of Sr46 in Aegilops tauschii, the diploid D genome progenitor of wheat - Naveenkumar Athiyannan; Yunming Long; Houyang Kang; Sutha Chandramohan; Dhara Bhatt; Qijun Zhang; Daryl L. Klindworth; Matthew N. Rouse; Timothy L. Friesen; Robert McIntosh; Peng Zhang; Kerrie Forrest; et al. (Theoretical and Applied Genetics, 2022)

Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Rohit Mago; Chunhong Chen; Xiaodi Xia; Alex Whan; Kerrie Forrest; Bhoja R. Basnet; Geetha Perera; Sutha Chandramohan; Mandeep Randhawa; Matthew Hayden; Urmil Bansal; Julio Huerta-Espino; et al. (Theoretical and Applied Genetics, 2022)

Land use intensification increasingly drives the spatiotemporal patterns of the global human appropriation of net primary production in the last century - Thomas Kastner; Sarah Matej; Matthew Forrest; Simone Gingrich; Helmut Haberl; Thomas Hickler; Fridolin Krausmann; Gitta Lasslop; Maria Niedertscheider; Christoph Plutzar; Florian Schwarzmüller; Jörg Steinkamp; et al. (Global Change Biology, 2022)
Land use has greatly transformed Earth's surface. While spatial reconstructions of how the extent of land cover and land‐use types have changed during the last century are available, much less information exists about changes in land‐use intensity. In particular, global reconstructions that consistently cover land‐use intensity across land‐use types and ecosystems are missing. We, therefore, lack understanding of how changes in land‐use intensity interfere with the natural processes in land systems. To address this research gap, we map land‐cover and land‐use intensity changes between 1910 and 2010 for 9 points in time. We rely on the indicator framework of human appropriation of net primary production (HANPP) to quantify and map land‐use‐induced alterations of the carbon flows in ecosystems. We find that, while at the global aggregate level HANPP growth slowed down during the century, the spatial dynamics of changes in HANPP were increasing, with the highest change rates observed in the most recent past. Across all biomes, the importance of changes in land‐use areas has declined, with the exception of the tropical biomes. In contrast, increases in land‐use intensity became the most important driver of HANPP across all biomes and settings. We conducted uncertainty analyses by modulating input data and assumptions, which indicate that the spatial patterns of land use and potential net primary production are the most critical factors, while spatial allocation rules and uncertainties in overall harvest values play a smaller role. Highlighting the increasing role of land‐use intensity compared to changes in the areal extent of land uses, our study supports calls for better integration of the intensity dimension into global analyses and models. On top of that, we provide important empirical input for further analyses of the sustainability of the global land system.

Projected climatic changes lead to biome changes in areas of previously constant biome - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2021)
Aim Recent studies in southern Africa identified past biome stability as an important predictor of biodiversity. We aimed to assess the extent to which past biome stability predicts present global biodiversity patterns, and the extent to which projected climatic changes may lead to eventual biome changes in areas with constant past biome. Location Global. Taxon Spermatophyta; terrestrial vertebrates. Methods Biome constancy was assessed and mapped using results from 89 dynamic global vegetation model simulations, driven by outputs of palaeoclimate experiments spanning the past 140 ka. We tested the hypothesis that terrestrial vertebrate diversity is predicted by biome constancy. We also simulated potential future vegetation, and hence potential future biome patterns, and quantified and mapped the extent of projected eventual future biome change in areas of past constant biome. Results Approximately 11% of global ice‐free land had a constant biome since 140 ka. Apart from areas of constant Desert, many areas with constant biome support high species diversity. All terrestrial vertebrate groups show a strong positive relationship between biome constancy and vertebrate diversity in areas of greater diversity, but no relationship in less diverse areas. Climatic change projected by 2100 commits 46%–66% of global ice‐free land, and 34%–52% of areas of past constant biome (excluding areas of constant Desert) to eventual biome change. Main conclusions Past biome stability strongly predicts vertebrate diversity in areas of higher diversity. Future climatic changes will lead to biome changes in many areas of past constant biome, with profound implications for biodiversity conservation. Some projected biome changes will result in substantial reductions in biospheric carbon sequestration and other ecosystem services.

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Global vegetation patterns of the past 140,000 years - Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Joy S. Singarayer; Paul J. Valdes; Brian Huntley (Journal of Biogeography, 2020)
Aim Insight into global biome responses to climatic and other environmental changes is essential to address key questions about past and future impacts of such changes. By simulating global biome patterns 140 ka to present, we aimed to address important questions about biome changes during this interval. Location Global. Taxon Spermatophyta. Methods Using the LPJ‐GUESS dynamic global vegetation model, we made 89 simulations driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 88 palaeoclimate experiments run using HadCM3. Experiments were run for 81 time slices between 1 and 140 ka, seven ‘hosing’ experiments also being run, using a 1‐Sv freshwater flux to the North Atlantic, for time slices corresponding to Heinrich Events H0–H6. Using a rule‐based approach, based on carbon mass and leaf area index of the LPJ‐GUESS plant functional types, the biome was inferred for each grid cell. Biomes were mapped, and the extent and total vegetation biomass of each biome, and total global vegetation biomass, estimated. Results Substantial changes in biome extents and locations were found on all vegetated continents. Although the largest magnitude changes were in Eurasia, important changes were seen in tropical latitudes and the Southern Hemisphere. Total global extent of most biomes varied on multi‐millennial (orbital) time scales, although some (e.g. Tropical Raingreen Forest) responded principally to the c. 100‐kyr glacial–interglacial cycle and others (e.g. Temperate Broad‐leaved Evergreen Forest) mainly to the c. 20‐kyr precession cycle. Many also responded to millennial contrasts between stadial (‘hosing’) and interstadial climates, with some (e.g. Tropical Evergreen Forest) showing stronger responses than to the multi‐millennial changes. Main conclusions No two time slices had identical biome patterns. Even equivalent Holocene and last interglacial time slices, and the last and penultimate glacial maxima, showed important differences. Only a small proportion of global land area experienced no biome change since 140 ka; many places experienced multiple biome changes. These modelling experiments provided little evidence for long‐term biome stability.

Genome-wide association reveals a complex architecture for rust resistance in 2300 worldwide bread wheat accessions screened under various Australian conditions - Reem Joukhadar; Grant Hollaway; Fan Shi; Surya Kant; Kerrie Forrest; Debbie Wong; Joanna Petkowski; Raj Pasam; Josquin Tibbits; Harbans Bariana; Urmil Bansal; German Spangenberg; et al. (Theoretical and Applied Genetics, 2020)

Global ecosystems and fire: Multi‐model assessment of fire‐induced tree‐cover and carbon storage reduction - Gitta Lasslop; Stijn Hantson; Sandy P. Harrison; Dominique Bachelet; Chantelle Burton; Matthias Forkel; Matthew Forrest; Fang Li; Joe R. Melton; Chao Yue; Sally Archibald; Simon Scheiter; et al. (Global Change Biology, 2020)
In this study, we use simulations from seven global vegetation models to provide the first multi‐model estimate of fire impacts on global tree cover and the carbon cycle under current climate and anthropogenic land use conditions, averaged for the years 2001–2012. Fire globally reduces the tree covered area and vegetation carbon storage by 10%. Regionally, the effects are much stronger, up to 20% for certain latitudinal bands, and 17% in savanna regions. Global fire effects on total carbon storage and carbon turnover times are lower with the effect on gross primary productivity (GPP) close to 0. We find the strongest impacts of fire in savanna regions. Climatic conditions in regions with the highest burned area differ from regions with highest absolute fire impact, which are characterized by higher precipitation. Our estimates of fire‐induced vegetation change are lower than previous studies. We attribute these differences to different definitions of vegetation change and effects of anthropogenic land use, which were not considered in previous studies and decreases the impact of fire on tree cover. Accounting for fires significantly improves the spatial patterns of simulated tree cover, which demonstrates the need to represent fire in dynamic vegetation models. Based upon comparisons between models and observations, process understanding and representation in models, we assess a higher confidence in the fire impact on tree cover and vegetation carbon compared to GPP, total carbon storage and turnover times. We have higher confidence in the spatial patterns compared to the global totals of the simulated fire impact. As we used an ensemble of state‐of‐the‐art fire models, including effects of land use and the ensemble median or mean compares better to observational datasets than any individual model, we consider the here presented results to be the current best estimate of global fire effects on ecosystems.

Extension of a haplotype-based genomic prediction model to manage multi-environment wheat data using environmental covariates - Sang He; Rebecca Thistlethwaite; Kerrie Forrest; Fan Shi; Matthew J. Hayden; Richard Trethowan; Hans D. Daetwyler (Theoretical and Applied Genetics, 2019)

Postsynaptic cutaneous vasodilation and sweating: influence of adiposity and hydration status - Matthew A. Tucker; Aaron R. Caldwell; Cory L. Butts; Forrest B. Robinson; Stavros A. Kavouras; Brendon P. McDermott; Tyrone A. Washington; Ronna C. Turner; Matthew S. Ganio (European Journal of Applied Physiology, 2018)

Pyramidal cell-selective GluN1 knockout causes impairments in salience attribution and related EEG activity - Alexandra D. Forrest; Jakyung Bang; Robert E. Featherstone; Jonathan H. Bloom; Matthew S. Luminais; Rebecca V. Zhang; Christopher R. Gajewski; Mary F. McMullen; Yuling Liang; Steven J. Siegel (Experimental Brain Research, 2018)

Effect of passive heat stress and exercise in the heat on arterial stiffness - Aaron R. Caldwell; Forrest B. Robinson; Matthew A. Tucker; Cash H. Arcement; Cory L. Butts; Brendon P. McDermott; Matthew S. Ganio (European Journal of Applied Physiology, 2017)

Exome sequence genotype imputation in globally diverse hexaploid wheat accessions - Fan Shi; Josquin Tibbits; Raj K. Pasam; Pippa Kay; Debbie Wong; Joanna Petkowski; Kerrie L. Forrest; Ben J. Hayes; Alina Akhunova; John Davies; Steven Webb; German C. Spangenberg; et al. (Theoretical and Applied Genetics, 2017)

Detection and validation of genomic regions associated with resistance to rust diseases in a worldwide hexaploid wheat landrace collection using BayesR and mixed linear model approaches - Raj K. Pasam; Urmil Bansal; Hans D. Daetwyler; Kerrie L. Forrest; Debbie Wong; Joanna Petkowski; Nicholas Willey; Mandeep Randhawa; Mumta Chhetri; Hanif Miah; Josquin Tibbits; Harbans Bariana; et al. (Theoretical and Applied Genetics, 2017)

Fine mapping of the chromosome 5B region carrying closely linked rust resistance genes Yr47 and Lr52 in wheat - Naeela Qureshi; Harbans Bariana; Kerrie Forrest; Matthew Hayden; Beat Keller; Thomas Wicker; Justin Faris; Elena Salina; Urmil Bansal (Theoretical and Applied Genetics, 2017)

The historic and extant spontaneous vascular flora of The New York Botanical Garden - Daniel E. Atha; Todd Forrest; Robert F. C. Naczi; Matthew C. Pace; Meryl Rubin; Jessica A. Schuler; Michael Nee (Brittonia, 2016)

Mapping of a new stem rust resistance gene Sr49 in chromosome 5B of wheat - Urmil K. Bansal; Sher Muhammad; Kerrie L. Forrest; Matthew J. Hayden; Harbans S. Bariana (Theoretical and Applied Genetics, 2015)

Potential impact of large ungulate grazers on A frican vegetation, carbon storage and fire regimes - Adrian Pachzelt; Matthew Forrest; Anja Rammig; Steven I. Higgins; Thomas Hickler (Global Ecology and Biogeography, 2015)
Aim Large ungulate grazers have been a fundamental component of A frican savannas since the spread of the savanna ecosystem in the M iocene. The magnitude of the impact of ungulates on vegetation has been debated for a long time, but quantifying such effects at the continental scale has been difficult. This study presents an attempt to estimate for the first time the potential impact of large natural ungulate grazer herds on A frican ecosystems. Location The A frican continent (excluding M adagascar). Method The potential impacts of grazing on grass biomass, competition between grasses and trees, the occurrence and effects of wildfire and biome distribution were simulated with a model that couples a physiological grazer population model with a physiological dynamic vegetation one (not including the effects of browsing). This model has previously been shown to reproduce grazer densities across A frican wildlife reserves. Results Modelled grazer densities corresponded reasonably well with the continental distribution of A frican grazers represented by the herbivore functional types in the model. The coupled model predicted a hump‐shaped relationship between annual precipitation and grazer biomass densities within a range of estimates from independent studies. In accordance with other studies, net primary productivity and the length of the dry season were the strongest predictors of grazer densities in the model. The inclusion of grazers in the model did not substantially alter an already (without grazers) reasonable fit between simulated vegetation biomass and burned area and estimates of these derived from remote sensing data. Nevertheless, the grazer–vegetation model predicted substantial impacts on grass biomass, tree biomass and burned area, particularly in areas with high grazer densities. The biome distribution at the continental scale, however, was similar with and without grazers. Main conclusion The results suggest that natural large ungulate grazers have been important drivers of ecosystem functioning in some savanna ecosystems, but also that they do not have a large effect on the continental‐scale biome distribution and carbon stocks.

Identification of a stem rust resistance locus effective against Ug99 on wheat chromosome 7AL using a RAD-Seq approach - Vincent Pujol; Kerrie L. Forrest; Peng Zhang; Matthew N. Rouse; Matthew J. Hayden; Li Huang; Linda Tabe; Evans Lagudah (Theoretical and Applied Genetics, 2015)

Scaling categorical spatial data for earth systems models - Jaclyn M. Hall; Caroline G. Staub; Matthew P. Marsik; Forrest R. Stevens; Michael W. Binford (Global Change Biology, 2015)

QTL for resistance to root lesion nematode (Pratylenchus thornei) from a synthetic hexaploid wheat source - Katherine J. Linsell; Muhammad S. Rahman; Julian D. Taylor; Rowena S. Davey; Beverley J. Gogel; Hugh Wallwork; Kerrie L. Forrest; Matthew J. Hayden; Sharyn P. Taylor; Klaus H. Oldach (Theoretical and Applied Genetics, 2014)

Chitosan-Alginate Scaffold Culture System for Hepatocellular Carcinoma Increases Malignancy and Drug Resistance - Matthew Leung; Forrest M. Kievit; Stephen J. Florczyk; Omid Veiseh; Jennifer Wu; James O. Park; Miqin Zhang (Pharmaceutical Research, 2010)